Constraints on the Galactic bar with RAVE. Issue Volume 9:Issue S298(2013) (6th January 2014) - Antoja, T.; Helmi, A.; ,
Abstract: We derive the pattern speed of the Galactic bar from the analysis of the kinematics of the Hercules stream at different Galactocentric radii with RAVE, assuming that Hercules is caused by the bar. We find a well constrained pattern speed of Ωb =1.98 +0.04 −0.08 Ωo, where Ω0 is the local circular frequency.